Diseño de un circuito sumador completo usando evolución intrínseca de hardware - Luna, José M; Devia, Christian J; Betancourt Uscátegui, Álvaro (Ingeniería, 2003)
This paper describes the use of bioinspired strategies in the design of a digital circuit, which implements a full adder with carry input on a programmable logic device, as well as presenting the development of an experimental evolvable hardware platform used in the experiment execution.